Voltage Variation Analysis By Using Gabor Transform - Abdullah, Abdul Rahim; Tee, Wei Hown; Yusoff, Mohd Rahimi (IJHATI, 2019)
Abstract—Voltage variations which include voltage sag, swell and interruption are simulated and analyzed in this paper. The signals are generated by implementing parametric equation in MATLAB. Simulated signals are studies by using time-frequency distribution (TFD) technique. The TFD method used in this paper is the Gabor transform which is less applied by the researchers. The signal parameters used in this paper are the RMS voltage and instantaneous power can be extracted from the TFR to study the distinctives of the voltage variations. The parameters extracted can detect the voltage variation signals successfully. The voltage variation signals are successfully detected by using the K-Nearest Neighbors (kNN) algorithm with the implementation of signal parameters extracted as the input on the classifier. The voltage variations waveforms as well as the signal parameters obtained are suitable to be further analyzed.